love of work or addiction? Understanding workaholics (Salud, Arte y Cuidado, 2026)
Workaholism is defined as a person working more than their job requires. Although there is no specific medical definition, it is associated with some forms of stress and obsessive-compulsive personality disorders. One of the key elements in workaholism is the person's denial of what is happening to them. The addict has a type A behavior pattern by being constantly involved in an excessive and chronic struggle to achieve an unlimited number of goals in the shortest possible time, even against the opinion of other people or the circumstances that surround them, coming to believe the justifications they resort to when faced with complaints from their family or coworkers. Their efforts are more than what is expected by their superiors, neglecting their health and work-life balance, generating negative consequences. However, despite everything, there are also positive consequences expressed in job satisfaction and respect in the workplace. Several basic characteristics determine people with this addiction, such as working compulsively, focusing on their work more than the process, the inability to relax after work, presenting a need to be in control and to do things their way, and giving greater importance to work than to relationships with others. To measure workaholic status, there are various self-report questionnaires, such as the WO-5, WART, and DUWAS, among others. In conclusion, workaholism is a topic that urgently needs further study by experts. It is imperative to recognize the presence of this disorder in workers in order to establish prevention and intervention strategies.
Keywords: workaholics; addiction; work; organization